Person-centered Maternity Care Among Mothers Who Gave Birth in South Wollo Zone Public Hospitals, Northeastern Ethiopia: A Mixed-method Study - Fentaw Teshome Dagnaw; Kiddus Yitbarek Kehali; Tesfamichael Alaro Agago; Habtamu Shimels Hailemeskel (SAGE Publishing, 2022)
Background: Globally, less attention has been given to the abuse and disrespect observed during maternity care. Person-centered maternity care is providing care that is respectful and responsive to individual women's preferences and needs and that their values guide all clinical decisions during childbirth. In Ethiopia, person-centered health care is one of the factors that increase client satisfaction and health service utilization. Therefore, we aimed to determine the level of person-centered maternity care among mothers who gave birth in health facilities of South Wollo Zone public hospitals, Northeastern, Ethiopia, 2019 using a mixed-method study. Methods: An institution-based cross-sectional study was conducted using both qualitative and quantitative data collection methods. Three hundred sixty-nine study participants were selected for the quantitative study using simple random sampling. Twelve study participants were selected for the qualitative study using purposive sampling. The quantitative data was coded and entered into Epi data 4.4 version and the analysis was carried out using Statistical Package for Social Sciences version 23. Descriptive statics was presented using tables and figures. Thematic analysis was used for qualitative data and presented with the quantitative result through triangulation. Result: The Percentage mean score of the person-centered maternity care scale of the respondents was 64% of the total expected score. Whereas, the percentage means score sub-scales were 81.9%, for dignity and respect, 56.4% for communication and autonomy and 61.6% for supportive care. Most mothers who participated in an in-depth interview reported that there is not enough bed, delivery coach and bedpan in government hospitals. Conclusion and recommendations: Person-centered maternity care in health facilities of South Wollo Zone public hospitals is low. Therefore, responsible health sectors should work to improve the quality of care through effective communication between clients and providers and a supportive environment is crucial to succeeding in increasing the uptake of high-quality facility-based births.